Complement-Mediated Microglial Clearance of Developing Retinal Ganglion Cell Axons - Tyler, Carolyn M. (2012)
In many parts of the developing vertebrate nervous system, axons are pruned to establish mature patterns of connectivity. In this issue of Neuron, Schafer et al. (2012) show that microglia may play a role in developmental axon pruning in the thalamus by engulfing presynaptic retinal ganglion cell terminals via a C3- and CR3-dependent mechanism.